(untitled) (Actualizaciones en Sida e Infectología, 2019)
Introduction: Despite the incidence of community-acquired pneumonia (CAP) due to community acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) being less than 10%, its presence should be considered in critical patients because of its high rate of mortality. Objectives: To identify risk factors associated with CA-MRSA in patients with severe CAP. Materials and method: A retrospective, observational study analysed episodes of etiological diagnosis in patients admitted in Intensive Care Unit in a public hospital between 2006 and 2017. Results: 250 episodes of NAC were included, among which 53 were caused by SAMR-AC and 197 by other agents. Patients with MRSA were the youngest (35.6±13.4 vs 43.1±12.4, p<0.001), and showed higher rates of skin and skin-structure infections (SSSI) (58.4% vs 2.0%, p<0.001), empyema (15.9% vs 5.0%, p=0.006), bilateral radiological compromise (81.1% vs 36.0%, p<0.001), average base-line APACHE II score (16.7±3.8 vs 13.2±4.3, p<0.001) and mechanical ventilation requirement rate (MV) (33.9 vs 17.6 p=0.009). The mortality rate was significantly higher than the one in CA-MRSA patients (35.8% vs 11.1%, p<0.001). The variables associated with CA-MRSA were SSSI (OR 67.99, IC 5% 21.94-210.65), bilateral radiological compromise (OR 7.63, IC 95% 3.67-16.11), APACHE II score ≥ 15 (OR 4.37, IC 95% 2.08-9.16), age ≤35 years (OR 3.60, IC 95% 1.77-7,29), empyema (OR 3.32, IC 95% 1.24-8.10) and MV (OR 2.85, IC 95% 1.36-5.86). Conclusion: The presence of SSSI, bilateral radiological compromise, APACHE II score ≥ 15, age ≤35 years, empyema and MV in patients with severe CAP was largely associated with higher probability of CA-MRSA infection.